Landscape-scale cropping changes in the High Plains: economic and environmental implications - Rosenzweig, Steven T., author; Schipanski, Meagan E., author; IOP Publishing Ltd, publisher (Colorado State University. Libraries, 2019)
A global transformation in semi-arid cropping systems is occurring as dryland (non-irrigated) farmers in semi-arid regions shift from crop rotations reliant on year-long bare fallows, called summer fallow, to more intensively cropped systems. Understanding the rate of cropping system intensification at the landscape scale is critical to estimating the economic and environmental implications of this movement. Here, we use high-resolution satellite data to quantify dryland cropping patterns from 2008 to 2016 in the US High Plains. We use these estimates to scale up our previous field-level research in this region on soil carbon, herbicide use, yields, and profitability. Over the nine year study period, the High Plains witnessed a profound shift in cropping systems, as the historically dominant wheat-fallow system was replaced by more intensified rotations as the dominant systems by land area. Out of the 4 million hectares of non-irrigated cropland in the study area, this shift coincided with a 0.5 million-hectare decline in summer fallow and a concurrent increase in alternative (non-wheat) crops. We estimate that, from 2008 to 2016, these patterns resulted in a 0.53 Tg (9%) increase in annual grain production, 80 million USD (10%) increase in annual net farm operating income, substantial reductions in herbicide use, and an increase in C sequestration that corresponds to greenhouse gas reductions of 0.32 million metric tons of CO2 equivalents per year (MMTCO2e yr-1). We project each of these implications to a scenario of potential maximum 100% intensification and estimate that, relative to 2016 levels, herbicide use would be reduced by more than half, grain production would increase by 25%, net operating income would increase by 223 million USD (26%), and greenhouse gases would be reduced by an additional 0.8 MMTCO2e yr-1. The scale of cropping intensification in the High Plains and its environmental and economic impacts has important implications for other regions undergoing similar transformations, and for policy that can either support or hinder these shifts toward more sustainable cropping systems.
This is an Accepted Manuscript of an article published by IOP Publishing, Ltd in Environmental Research Letters on 19 December 2019, available at: https://doi.org/10.1088/1748-9326/ab5e8b.